TRANSFORMASI KEPEMIMPINAN KIAI DALAM MENARIK MINAT MASYARAKAT: STUDI PADA PONDOK PESANTREN MAMBAUL ULUM - Moh. Rifa’i; Dian Hidayatullah Farchani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
This study aims to analyze the role of kiai leadership in increasing public interest in using educational services at the Mambaul Ulum Islamic Boarding School in the midst of increasingly competitive competition from educational institutions. The research uses a qualitative approach with a case study design, with data obtained through observation, in-depth interviews, and documentation of kiai, pesantren administrators, teachers, guardians of students, students, and community leaders, then analyzed using the Miles and Huberman model. The results of the study show that kiai leadership plays a significant role in increasing public interest through three main aspects, namely building a positive image of pesantren through moral example, developing educational services that are adaptive and in accordance with community needs, and strengthening social relationships through communication and active involvement in community life. These three aspects are integrated with each other in building public trust which is a key factor in determining the choice of pesantren education services. These findings confirm that the success of pesantren is not only determined by the quality of the educational program, but also by the leadership capacity of the kiai in building trust, a positive image, and harmonious social relations, thereby making a theoretical contribution to the development of Islamic education leadership studies as well as practical implications for improving the competitiveness of Islamic boarding schools.